Validation and psychometric testing of the Chinese version of the prenatal body image questionnaire - Qiaosong Wang; Jingjing Lin; Qirong Zheng; Liping Kang; Xueling Zhang; Kun Zhang; Rong Lin; Rongjin Lin (BMC Pregnancy and Childbirth, 2024)
Abstract Background The body image during pregnancy potentially affects both short- and long-term maternal and child health outcomes, including pregnancy mood, postpartum weight recovery, and the quality of mother–child interactions. However, research on the impact of body changes during pregnancy in the Chinese population is scarce. A comprehensive, practical, and reliable tool for assessing pregnant women is needed to detect, intervene in, and implement the reduction of physical dissatisfaction risk. This study translated the Prenatal Body Image Questionnaire (PBIQ) into the Chinese version (PBIQ-C) to assess the body image of pregnant women and evaluated its reliability and validity. Methods An improved Brislin translation model was used for the translation. A panel of experts determined the content validity. A convenience sample of 429 pregnant women was chosen from three third-class hospitals in different regions of Fujian Province, China. Factor analysis, Pearson’s correlation, retest reliability, and Cronbach’s alpha were employed to evaluate structural validity and reliability. Results The final PBIQ-C had five dimensions with 21 items. Exploratory factor analysis obtained a five-factor solution, which accounted for a total of 60.34%. Confirmatory factor analysis showed that the model fit of the five-factor model also reached a satisfactory model fit after modifying: The Comparative Fit Index was 0.93, and the Tucker-Lewis Index was 0.92; the Root Mean Square Error of Approximation was 0.079. The content validity index of the scale ranged from 0.63 ~ 1.00. The Cronbach’s alpha coefficient was 0.95 for the total scale, and the test–retest reliability was 0.80. Conclusions The findings indicated that the PBIQ-C is a valid and reliable instrument for assessing women’s body image during pregnancy, which helps in the early identification of body dissatisfaction during pregnancy and enables the early prevention of postpartum depression.